Investigation of the column performance of cadmium(II) biosorption by Cladophora crispata flocs in a packed bed - Aksu, Z; Ozer, D; Ozer, A; Kutsal, T; Caglar, A (Taylor & Francis Inc, 1998)
In this study the biosorption of cadmium(II) ions to dried flocs of Cladophora crispata, a kind of green algae, was investigated in a packed bed column. The cadmium(II) removal performance of the column was investigated as a function of the cadmium(II)-bearing solution flow rate and the inlet cadmium(II) concentration. Removal and total removal percentages of cadmium(II) related to flow volume were determined by evaluating the breakthrough curves obtained at three different flow rates for two different constant inlet concentrations. At the lowest flow rate the effect of inlet cadmium(II) concentration on the column capacity was also investigated. Data confirmed that early saturation and lower cadmium(II) removals were observed at higher flow rates and at higher cadmium(II) concentrations. Column experiments also showed that maximum specific cadmium(II) uptake values of C, crispata flocs were as higher as those of other biomass sorbents.
Keywords: packed bed column; flocs of Cladophora crispata; cadmium(II) biosorption